The Influence of School Climate, Teachers' Commitment, Teachers' Motivation on Teachers' Work Performance Through Teachers' Job Satisfaction - Evonne Lai Eng Fei; Crispina Gregory K Han (2019)
The purpose of this study is to examine the influence of school climate, teachers’ commitment, teachers’ motivation on teachers’ work performance through teachers’ job satisfaction as a mediator. The sample used in this study consisted of 2738 responses from Sarawak secondary school teachers collected through a structured questionnaire. The study used Partial Least Square (PLS) analysis technique using the Smart-PLS 3.2.7 software. Findings confirmed that school climate, teachers’ commitment, teachers’ motivation, and teachers’ job satisfaction were the key constructs for increasing teachers’ work performance among secondary school teachers in Sarawak. Furthermore, the importance-performance matrix analysis (IPMA) has shown that teachers’ job satisfaction was the most important factor. The study results also stated that teachers’ job satisfaction mediates the relationship between school climate and teachers’ work performance; teachers’ commitment and teachers’ work performance; and teachers’ motivation and teachers’ work performance.